Spatial Congruity Effects Reveal Metaphorical Thinking, not Polarity Correspondence - Dolscheid, Sarah; Casasanto, Daniel (Frontiers in Psychology, 2015)
Spatial congruity effects have often been interpreted as evidence for metaphorical thinking, but an alternative account based on polarity correspondence (a.k.a. markedness) has challenged this view. Here we compared metaphor- and polarity-correspondence-based explanations for spatial congruity effects, using musical pitch as a testbed. In one experiment, English speakers classified high- and low-frequency pitches as “high” and “low,” or as “front” and “back,” to determine whether space-pitch congruity effects could be elicited by any marked spatial continuum. Although both pairs of terms describe bipolar spatial continuums, we found congruity effects only for high/low judgments, indicating that markedness is not sufficient to produce space-pitch congruity effects. A second experiment confirmed that there were no space-pitch congruity effects for another pair of terms that have clear markedness (big/small), but which do not denote spatial height. By contrast, this experiment showed congruity effects for words that cued an appropriate vertical spatial schema (tall/short), even though these words are not used conventionally in English to describe pitches, ruling out explanations for the observed pattern of results based on verbal polysemy. Together, results suggest that space-pitch congruity effects reveal metaphorical uses of spatial schemas, not polarity correspondence effects.